INTEGRATION OF NETWORK CAPABILITIES OF BLENDED LEARNING - Pivneva, Svetlana; Vitkovskaya, Nataliaya; Makarov, Oleg; Benikovna, Dobrova (Revista Inclusiones, 2020)
Today, most universities stick to traditional forms of organization of learning. However, the processes of informatization and ubiquitous computerization are irreversible and involve significant changes in organizational forms. The level of development of ICT tools and the active introduction of computer-based learning indicate that digital education is becoming a traditional way of gaining knowledge among most countries of the world. The study defines the prerequisites for the introduction of blended learning based on ICT; theoretical analysis of the concept and features is carried out. ased on an expert survey, the integration of the network capabilities of blended learning is analyzed. It is based on the integration of online services in the information and educational environment of higher education institutions, the implementation of a cloud-based environment in the process of organizing the learning process, and the use of network capabilities in organizing pedagogical interaction between teachers and students in blended learning.